Students' perceptions towards peer feedback approach in a Malaysian English as a second language (ESL) classroom / Misyana Susanti Husin and Kamisah Hj Ariffin - Husin, Misyana Susanti; Hj Ariffin, Kamisah (Universiti Teknologi MARA Cawangan Pahang, 2008)
Peer feedback is one of the commonly practised pedagogical approaches in writing classes. It can be seen as a powerful tool to provide students with an authentic audience who give different views on their writings and, thus, able to increase the student writers' confidence and motivation. The aim of this exploratory classroom study was to investigate how peer feedback was valued in a writing course. It also explored the potential benefits of peer feedback application in the writing class. The findings reveal that peer feedback was well-received by the students as it gave them the benefits of additional point of views from a wider audience. However, the findings also show that peers' linguistic competence, attitude and cultural values could affect the value and validity of the feedback which, in turn, could affect the effectiveness of this approach.